Research progress on the prevention and treatment of zearalenone poisoning in animals using natural products - Liu, Nannan; Zhang, Qi; Piao, Yulan; Sun, Chenghe; Shi, Guangliang (Frontiers in Veterinary Science, 2025)
Zearalenone (ZEA) is a non-steroidal estrogenic mycotoxin produced by Fusarium fungi, widely present in cereal feeds such as corn, barley, wheat, and sorghum. It not only impacts agricultural production and feed safety but also poses a serious threat to animal health. Extensive research demonstrates that natural products can effectively mitigate the toxic effects of zearalenone. This paper reviews zearalenone’s physicochemical properties and toxicological effects, with a focus on advances in the research on reducing zearalenone toxicity through plant, microbial, and mineral-derived natural products. The aim is to provide theoretical references for developing more efficient and safer zearalenone detoxification agents.